Considerations on proper nutrition during pregnancy - Cereceda Bujaico, María del Pilar (2014)
Nutrition plays a key role in the development of the future baby during pregnancy and lactation. Following conception maternal adaptation processes include physiological, biochemical and metabolic changes that require increasing nutritional needs. Failure to meet nutritional needs during pregnancy may be related to prematurity and neonatal morbidity and mortality. Information on dietary guidelines for pregnant woman presented in this article is expected to be useful to health care providers for proper guidance on maternal nutrition.